Pengendalian Lidah sebagai Tanggung Jawab Spiritualitas Kristen: Studi Yakobus 3:1-12 - Amita Prissila; Frans Aliadi; Sefira Sefira (Pusat Riset dan Inovasi Nasional, 2025)
The tongue is a small part of the body that holds significant power to influence both individual life and community well-being. James 3:1–12 provides a firm warning about the dangers of an uncontrolled tongue, depicting it as a fire, a world of evil, and deadly poison. This study aims to examine the meaning of controlling the tongue as a responsibility of Christian spirituality through a literature review and exegetical-hermeneutical analysis of James 3:1–12. This qualitative research employs primary data from the biblical text (Indonesian Bible Society version and the Greek text) and secondary data from commentaries, Christian ethics books, and theological journals. The findings indicate that controlling the tongue is a sign of spiritual maturity and an essential aspect of Christian discipline that must be continuously cultivated. Disciplined speech reflects living faith and serves as a means to foster love, truth, and peace within the community. This study highlights the need for churches and believers to integrate ethical speech as a core part of their witness in the world.